A Study on Determining Protein Level in Diet of Partridge (Alectoris chukar) During Growing Period (0-4 Wk) - Sengul, Turgay; Cetin, Mehmet; Sogut, Bunyamin; Gurbuz, Yavuz (International Journal of Poultry Science, 2006)
This study was conducted to determine growth performance of partridge (A. chukar) fed by diets include different level of CP through 0-4 weeks of age. First, second, third and fourth groups had 28, 26, 24 and 22 % CP in diet, respectively. At the end of 4 weeks of growth period, live weights of group 1, 2, 3 and 4 were 125,8, 128.6, 124.6 and 120.4 g for males, 113.4, 111.3, 110.3 and 105.2 g for females, respectively. Protein levels in diet had significant effect on live weight at 1st and 3rd week of age only. However, sex had significant (P< 0.001) effects on live weight of the birds through growth period. Different CP level in diet did not affected weekly and cumulative feed consumption significantly. Through 0-4 week of age, cumulative feed consumption of the groups was 194.7, 190.8, 195.6 and 185.5 g for group 1st, 2nd, 3rd and 4th, respectively. Differences among the groups in terms of FCR were significant (P< 0.05) at 1st week of age only, and birds fed by diet includes 26 % CP had the best FCR at this week. FCR of the 1st, 2nd, 3rd and 4th treatment groups were calculated as 1.85, 1.81, 1.83 and 1.89, respectively. As a result, it could be said that 28, 26, 24 and 22 % CP level in diet did not affect growth performance of partridges through 0-4 weeks of age when taking account live weight, feed consumption and FCR of the partridge.